2019
DOI: 10.1111/hepr.13392
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of lusutrombopag in Japanese chronic liver disease patients with thrombocytopenia undergoing invasive procedures: Interim results of a postmarketing surveillance

Abstract: Aim Lusutrombopag is approved for the treatment of thrombocytopenia in chronic liver disease patients undergoing invasive procedures. This real‐world surveillance assesses the safety and effectiveness of lusutrombopag in Japan. Methods This ongoing, multicenter, prospective, real‐world surveillance is collecting data from case report forms between October 2016 and May 2021. Interim data up to September 2018 were used to evaluate safety (adverse events and adverse drug reactions [ADRs]) and effectiveness (propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…16 The effect of three treatments with lusutrombopag was shown in the interim results of a post-marketing surveillance study. 17 However, to the best of our knowledge, studies in which lusutrombopag was given three or more times have not been reported, and this is the first report that describes the administration of lusutrombopag more than three times in patients with CLD.…”
Section: Discussionmentioning
confidence: 86%
“…16 The effect of three treatments with lusutrombopag was shown in the interim results of a post-marketing surveillance study. 17 However, to the best of our knowledge, studies in which lusutrombopag was given three or more times have not been reported, and this is the first report that describes the administration of lusutrombopag more than three times in patients with CLD.…”
Section: Discussionmentioning
confidence: 86%
“…The time course of PC in the non-naïve patients was similar to the profiles in lusutrombopag-naïve patients from previous reports. 19,20 The incidence of TEAEs was 75.0%. There were no thrombosis-related or bleeding-related AEs in non-naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, only a few reports describe the effect of lusutrombopag in patients being retreated with lusutrombopag. 19,20 This open-label study aimed to determine whether platelet monitoring and the discontinuation criteria could be applied at a reduced frequency without affecting clinical outcomes. Additionally, the efficacy, safety, and pharmacokinetics (PK) were evaluated in lusutrombopag-naïve and lusutrombopag retreatment (non-naïve) CLD patients with thrombocytopenia undergoing planned invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Lusutrombopag induces platelet production by acting on the transmembrane domain of the human TPO receptor and activating the signaling pathway in the same way as endogenous TPO (7). Lusutrombopag treatment efficiently increases platelet counts and makes it possible for patients with CLD and thrombocytopenia to receive invasive procedures (8)(9)(10)(11)(12). In this study, we assessed the efficacy of repeated lusutrombopag treatment and the factors associated with a response to lusutrombopag.…”
Section: Introductionmentioning
confidence: 99%